The blurred cut-off frequency of acoustic horns - Tomasz ZAMORSKI (Archives of Acoustics)
On the basis of discussion of the Webster equation the conditions and possibilities of a blurred cut-off frequency for horns of arbitrary geometry were analyzed. The transmission properties of horns in the blurred region were discussed. Subsequently the blurred cut-off frequency was considered for hyperbolic horns of annular cross-section.